A snapshot of 26 years of research on creativity in software engineering - A systematic literature review - Amin, A. (Springer Verlag, 2018)
Creativity is important for software engineering. It is expected to gain more importance in coming decades. However the research work on creativity in software engineering is scattered and scarce. The current study aims to systematically review the existing literature on creativity in software engineering. As a result, the current study has highlighted 26 years of research work on creativity in software engineering. From the 49 selected studies, nearly half addressed creativity only in requirement engineering phase. Hence, it is safe to assume that there is a lack of research work on creativity in other phases of software development. Â© Springer Science+Business Media Singapore 2018.